Early Warning Indicators for Norwegian Banks: A Logit Analysis of the Experiences from the Banking Crisis - Sigbjørn Atle Berg; Barbro Hexeberg (Norges Bank, 1994)
Most existing early warning studies for the banking industry are based on U.S. data. The present paper considers the experiences made during the Norwegian banking crisis 1988- 92. The performance of a set of possible early warning indicators are evaluated, both as independent indicators and as part of a simultaneous indicator system. The paper leads to recommendations for the future structure of early warning systems, specifically with reference to the Norwegian banking industry but with relevance even to the banking industries of other countries.
hdl:11250/2500584
Keywords: 330